Expression of the inhibitory receptor NKG2A correlates with increased liver and splenic NK cell response to activating receptor engagement. Issue 2 (24th March 2017) - Meyer, Claire E.; Key, Phillip N.; Zhu, Toby; Shabsovich, Mark; Ni, Ann; Tripathy, Sandeep K.
Abstract: Introduction: Natural killer (NK) cells play a critical role in the innate immune response to viruses and tumors, and comprise a large proportion of the hepatic lymphocyte population. They must remain tolerant to non‐pathogenic antigens while protecting the host from harmful agents. Herein, we investigate how the NK cell response to activation receptor engagement is altered in the liver. Methods: In this study, we assess IFN‐γ production and degranulation of splenic NK cells and selected subsets of liver NK cells. Flow cytometry (FCM) was used to asses IFN‐γ production and degranulation following stimulation of the NK cells with plate bound antibodies to activating receptors. Results: We show that smaller percentages of hepatic NK cells produce interferon (IFN)–γ and/or degranulate than do splenic NK cells upon stimulation through activating receptors. We also found that smaller percentages of the circulating NK (cNK) cells in the liver produce IFN‐γ and/or degranulate, compared to the liver tissue resident NK (trNK) cells. In addition, IFN‐γ production by liver cNK cells is not increased in IL‐10 deficient mice, suggesting that their hyporesponsiveness is not mediated by the presence of this anti‐inflammatory cytokine in the hepatic microenvironment. On the other hand, liver trNK cells express higher levels of the inhibitory receptor NKG2A than do cNK cells, correlating with their increased IFN‐γ production and degranulation. Conclusions: Liver cNK cells' hyporesponsiveness to stimulation through activating receptors is independent of IL‐10, but correlates with decreased NKG2A expression compared to trNK cells. In addition, we demonstrate that liver NK cells become further hyporesponsive upon continuous engagement of an activating receptor on their cell surface. Abstract : Liver NK cells produce less IFN‐Y upon stimulation of activating receptors than splenic NK cells. This appears to be due to decreased production by circulating NK rather than resident NK cells within the liver and correlates with expression of NKG2A.